2022
DOI: 10.1111/opo.13047
|View full text |Cite
|
Sign up to set email alerts
|

Wavefront aberrometry repeatability and agreement—A comparison between Pentacam AXL Wave, iTrace and OPD‐Scan III

Abstract: Introduction To compare intrasession agreement and repeatability of wavefront aberration measurements from three different aberrometers obtained using Hartmann–Shack, ray tracing and automated retinoscopy methods, as well as their interdevice agreement. Methods Three consecutive measurements were obtained using the Pentacam AXL Wave, the iTrace and the OPD‐Scan III in 47 eyes of 47 patients. Wavefront refractions, root mean square of total aberrations (RMS total), RMS of higher‐order aberrations (HOA) and seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…This result was believed to be because of the smaller measurement values and narrower standard deviations in the control group, resulting in smaller ICC values in the control group than in the KC group. Overall, as reported by Kundu et al 21,22 good intrasubject repeatability was found in healthy eyes and eyes with KC.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…This result was believed to be because of the smaller measurement values and narrower standard deviations in the control group, resulting in smaller ICC values in the control group than in the KC group. Overall, as reported by Kundu et al 21,22 good intrasubject repeatability was found in healthy eyes and eyes with KC.…”
Section: Discussionsupporting
confidence: 79%
“…Recently, several researchers have reported on the repeatability and agreement of the device used herein compared to other devices for wavefront measurement. [19][20][21][22][23] Thus far, there have been two reports on wavefront analysis in KC using this wavefront aberrometer, but both are simple comparisons with healthy eyes. 21,23 Consistent with the result of our previous investigation that used an integrated Placido-disk topography system with a Hartmann-Shack wavefront aberrometer, 15 wavefront properties generally correlated with KC severity classified based on clinical and topographic signs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…WF aberration data for each subject were collected from an FDA approved and commercially available WF measurement device (Pentacam AXL Wave, Oculus Optikgeraete GmbH, Wetzlar, Germany), selected because of the good repeatability [ 19 , 20 ]. The main aberration data were collected for natural pupil conditions at a 3 mm diameter, with the HSP.…”
Section: Methodsmentioning
confidence: 99%
“…In other words, in addition to routine measurement, the evaluation of corneal parameters with wavefront analysis, including PK, TK and TNP, plays an important role in the preoperative assessment in cataract surgery, especially in eyes that have had prior refractive corneal surgery and in patients who desire a premium IOL [ 5 ]. Many systems with different principles, such as Hartmann–Shack, Tscherning, ray tracing (e.g., iTrace) and automated retinoscopy [ 6 ], have been widely used in clinical settings in recent years.…”
Section: Introductionmentioning
confidence: 99%